Estudio de factibilidad para la creación de una empresa prestadora de servicios especializados de lavandería para el sector hotelero y de restaurantes de la ciudad de Quito - Guamán Gaona, Liliana Paola (2013)
This project analyzes the feasibility to create a business which will be specialized in laundry services to hotel sector and restaurants in Quito. This investigation document is comprised of six chapters as the description next: First, the project describes the components and technical support to create the business, such as: industry analysis, service description, and an environment analysis. The second chapter contains the market study. It determines the offer and demand to the laundry service considering the target. It uses polls to know how the consumers act. Also, it analyzes the strategic and marketing structure to the business.